Role of the Side Chain in the Phase Segregation of Polymer:Fullerene Bulk Heterojunction Composites. Issue 12 (23rd July 2013) - Kim, Heejoo; Lee, Byoung Hoon; Lee, Kyu Cheol; Kim, Geunjin; Yu, Jin Young; Kim, Nara; Lee, Seoung Ho; Lee, Kwanghee
<x xml:space="preserve">Abstract</x> The correlation between the geometrical structural change in push‐pull π‐conjugated polymers and the formation of phase segregation in their bulk heterojunction (BHJ) composite films is investigated. When substituted with large alkyl side chains, the polymer wires experience serious conformational distortion by increasing the torsion energy of dihedral angles along the backbone and undergo large‐scale phase segregation in the BHJ composites. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>